Effects of Jintiange on the healing of osteoporotic fractures in aged rats - Jie Liu; Ting-Ting Liu; Hai-Cheng Zhang; Chen Li; Wei Wei; Ai-Jun Chao (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Objective To examine the effects of Jintiange on enhancing the healing of osteoporotic fractures in aged rats. Methods An osteoporotic fracture model of femur was established using 70 SD rats (aged > 12 months), which were randomly numbered and divided into an experimental group and a control group, each with an equal sample size (n = 35). The experimental group received Jintiange capsule ingredients via intragastric administration, while the control group received an equal volume of saline via the same method. X-ray examinations were conducted at the 4th and 12th weeks to evaluate fracture healing in the rats. After 12 weeks, micro-CT scanning was employed to assess the microstructure of the healthy femurs, and the parameters of the experimental and control groups were compared. Results After 4 weeks, the mean fracture healing scores were 0.78 ± 0.43 in the experimental group and 0.56 ± 0.51 in the control group. After 12 weeks, the mean scores were 1.50 ± 0.71 in the experimental group and 0.96 ± 0.68 in the control group. The scores in the experimental group were higher than those in the control group (P < 0.05). Micro-CT examination of the femurs showed an improvement trend in bone microarchitecture in the experimental group, indicated by increased bone volume fraction (BV/TV), trabecular number (Tb. N), and trabecular thickness (Tb. Th). However, these improvements were not statistically significant. A negative correlation with statistical significance was observed between trabecular separation (Tb. Sp) and fracture healing scores. Conclusions Jintiange may promote osteoporotic fracture healing in aged rats by enhancing bone microstructure.